Isolation and Detection of Erysipelothrix rhusiopathiae and Its Distribution in Humans and Animals by Phenotypical and Molecular Methods in Ahvaz-Iran in 2015 - Pariya Ahmadi Balootaki; Mansour Amin; Farkhondeh Haghparasti; Farokh Rokhbakhsh-Zamin (Iranian Journal of Medical Sciences, 2017)
Background: Erysipelothrix rhusiopathiae (E. rhusiopathiae) is generally transmitted into the gastrointestinal tract of animals by the intake of contaminated food or water and causes great economic loss in agriculture worldwide. Some of the Erysipelothrix spp. are the causative agents of erysipeloid, which is an occupational infection in humans. The aim of the present study was to isolate E. rhusiopathiae from animals as well as the hands of the butchers working in Ahvaz, Iran, and to determine their susceptibility to antibiotics. Methods: Totally, 150 samples were taken from slaughterhouse workers, fishermen, and livers and hearts of sheep and calves by the swabbing method. Phenotypical methods and polymerase chain reaction (PCR) were used for the isolation and identification of E. rhusiopathiae. The isolates were tested for their susceptibility to commonly used antimicrobial agents using the disk diffusion protocol described by the Clinical and Laboratory Standards Institute. Results: Out of the 150 samples examined via phenotypical and biochemical tests, 16 samples were positive as putative Erysipelothrix spp. twelve cases out of the 16 putative Erysipelothrix spp. were confirmed by PCR. The tested isolates were highly sensitive to the antibiotics used. The results of the sensitivity and specificity of PCR revealed that the sensitivity and specificity of indirect PCR were higher than those of direct PCR. Conclusion: E. rhusiopathiae is widely distributed on seafood and presents as a commensal pathogen in nature and animals. Infection with this microorganism should be emphasized because it is a rare organism causing severe infections such as infectious endocarditis and polyarthritis following localized infections.